2010
DOI: 10.4314/ejc.v2i2.60850
|View full text |Cite
|
Sign up to set email alerts
|

Drop out From School among Girls in Edo State: Implications for Counselling

Abstract: Drop out from school among girls is a global phenomenon. In Nigeria, girl's dropout from school for various reasons like early marriage, pregnancy, religious factors, socioeconomic factors, school related factors and ill health. The focus of this paper is to investigate why girls dropout from school in Edo State. The descriptive survey method was adopted for this study. A checklist on reasons for drop out was used in gathering information from the respondents. From a pool of primary schools, secondary schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
2
3
0
Order By: Relevance
“…Data analysis showed that poverty ranked highest (48%) amongst the barriers to girl-child education. This finding is in agreement with Obanya (2004), UNICEF (2007), Amosand (2011) and Alika and Egbochukwu (2009) who found poverty as a major barrier impacting on girl-child education. The analysis also showed that cultural/religious inclination (15%) accounting for the reason why the girl-child cannot access formal education.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…Data analysis showed that poverty ranked highest (48%) amongst the barriers to girl-child education. This finding is in agreement with Obanya (2004), UNICEF (2007), Amosand (2011) and Alika and Egbochukwu (2009) who found poverty as a major barrier impacting on girl-child education. The analysis also showed that cultural/religious inclination (15%) accounting for the reason why the girl-child cannot access formal education.…”
Section: Discussion Of Resultssupporting
confidence: 91%
“…In agreement with this findings, Thornberg (2010) lamented that students affected by bullying would be at risk of developing depression, anxiety, mistrust of others, loneliness, low self-esteem, poor social adjustment, poor health and poor academic achievement. The findings of this study on bullying capable of making students not to attend school corroborates that of Alika (2012) whose finding showed that a significant relationship existed between bullying and drop out from school. Furthermore, the findings revealed that bullying can make students to always ask for extra money from parents.…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…Girls describe this hampers their performance in school, leading to humiliation in class and punishment, lethargy towards engagement in class, absenteeism and, for some, eventual dropout. Girls in a study conducted in Nigeria ranked poor performance as the second major reason for dropout after poverty [ 48 ], with poor performance and grade repetition associated with pregnancy-related dropout in South Africa [ 27 ]. Loss of interest in schoolwork was also reflected in some narratives about boyfriends and peers who reinforced perceptions that girls who leave school can earn money or be supported through marriage.…”
Section: Discussionmentioning
confidence: 99%